1994
DOI: 10.1073/pnas.91.25.12003
|View full text |Cite
|
Sign up to set email alerts
|

Fialuridine accumulates in DNA of dogs, monkeys, and rats following long-term oral administration.

Abstract: Accumulation of the antiviral nucleoside analogue fraluridine (FIAU; 1-(2'-deoxy-2'-fluoro-P-D-arab- In part because of the lactic acidosis observed in the clinical trials, it has been proposed that FIAU may selectively affect mitochondrial function. Depletion of muscle mitochondrial DNA (mtDNA) has been observed with dideoxycytidine (ddC) (6) and 3'-azido-3'-deoxythymidine (AZT) (7) and has been suggested as a possible mechanism for the delayed toxicity of FIAU. Unlike AZT and ddC, however, FIAU has a free 3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…19,42 Comparable decreases in hepatic mtDNA were observed in monkeys, rats, and dogs treated with FIAU for 30, 70, and 90 days, respectively, but toxicity similar to that seen in humans and woodchucks was not observed. 43 Incorporation of FIAU into cellular DNA of humans 42 and the woodchucks described in the current study may have been important in determining FIAU toxicity, but no toxicity was reported in dogs 9 with comparable levels of FIAU integrated into cellular DNA or in rats 9,47 with levels of integrated FIAU that were 10 times higher than the levels formed in humans and woodchucks. Based on these observations, neither integration of FIAU into cellular DNA 9 nor decreased abundance of mtDNA can be considered sufficient to explain the toxicity of FIAU.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…19,42 Comparable decreases in hepatic mtDNA were observed in monkeys, rats, and dogs treated with FIAU for 30, 70, and 90 days, respectively, but toxicity similar to that seen in humans and woodchucks was not observed. 43 Incorporation of FIAU into cellular DNA of humans 42 and the woodchucks described in the current study may have been important in determining FIAU toxicity, but no toxicity was reported in dogs 9 with comparable levels of FIAU integrated into cellular DNA or in rats 9,47 with levels of integrated FIAU that were 10 times higher than the levels formed in humans and woodchucks. Based on these observations, neither integration of FIAU into cellular DNA 9 nor decreased abundance of mtDNA can be considered sufficient to explain the toxicity of FIAU.…”
Section: Discussionmentioning
confidence: 76%
“…[44][45][46] In studies of monkeys, rats, and dogs treated with FIAU, significant integration of FIAU was observed into cellular DNA in all three species. 9 In rats, the liver appeared to be a minor target for FIAU integration after 1 day, but after 77 days of FIAU treatment, the FIAU content of hepatic DNA was higher than the DNA of any other tissue. 47 Rats treated with 255 or 510 mg/kg of FIAU for 70 to 110 days had levels of FIAU incorporated into hepatic DNA that were 10-fold higher 9,47 than that observed in woodchucks in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations